PERGESERAN MASYARAKAT MELAYU DARI USAHAWAN MENJADI BIROKRAT DI KELURAHAN ALAI KECAMATAN UNGAR KABUPATEN KARIMUN - Nurmahfuzah Nurmahfuzah; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on Regional Regulation No. 02 of 2012 Alai Sub-District is part of Ungar Sub-district which is divided from Kundur District. Alai's name was only known around the 1930s. The majority of the Ungar people are Malays. Whereas a person is referred to as Malay when he is Muslim, daily speaks Malay and is culturally Malay. Meanwhile, Malay customs are a tradition that is syllable, syarak is based on the Kitabullah. The Alai Malay community, which initially had the livelihood of entrepreneurs, began to experience a shift into bureaucrats. The purpose of this study is (1) To find out a brief history of Malay society in Alai Sub-District, Ungar District, Karimun Regency. (2) To find out the shift of Malay society from businessmen into bureaucrats in Alai Village, Ungar District, Karimun Regency. (3) To find out the factors of shifting Malay society from businessmen into bureaucrats in Alai Village, Ungar District, Karimun Regency. The method used in this study is a qualitative descriptive method. While the data collection techniques used are library techniques. documentation techniques, interview techniques and observation techniques. The results of the study in general are that there has been a shift in Malay society from businessmen to bureaucrats in Alai Sub-District, Ungar District, Karimun Regency. Both in the form of intergenerational social mobility and intragenerational social mobility. Educational, economic, opportunity and family factors are factors that have led to a shift in Malay society from businessmen to become bureaucrats in Alai Sub-District, Karimun District.Key Words: Malay Society, Job Mobility